Privatization and bank performance in developing countries - Boubakri, Narjess; Cosset, Jean-Claude; Fischer, Klaus; Guedhami, Omrane (Journal of Banking & Finance, 2005)
We examine the postprivatization performance of 81 banks from 22 developing countries. Our results suggest that: (i) On average, banks chosen for privatization have a lower economic efficiency, and a lower solvency than banks kept under government ownership. (ii) In the postprivatization period, profitability increases but, depending on the type of owner, efficiency, risk exposure and capitalization may worsen or improve. However, (iii) Over time, privatization yields significant improvements in economic efficiency and credit risk exposure. (iv) We also find that newly privatized banks that are controlled by local industrial groups become more exposed to credit risk and interest rate risk after privatization.